Rates of Spinal Cord Infarction After Repair of Aortic Aneurysm or Dissection. Issue 8 (August 2017) - Gialdini, Gino; Parikh, Neal S.; Chatterjee, Abhinaba; Lerario, Michael P.; Kamel, Hooman; Schneider, Darren B.; Navi, Babak B.; Murthy, Santosh B.; Iadecola, Costantino; Merkler, Alexander E.
Abstract : Background and Purpose—: The rate of spinal cord infarction (SCI) after surgical or endovascular repair of an aortic aneurysm or dissection is unclear. Methods—: Using administrative claims data, we identified adult patients discharged from nonfederal acute care hospitals in California, New York, and Florida who underwent surgical or endovascular repair of an aortic aneurysm or dissection between 2005 and 2013. Patients with SCI diagnosed before the aortic repair were excluded. Our primary outcome was an SCI during the index hospitalization for aortic repair. Descriptive statistics were used to estimate crude rates of SCI. Analyses were stratified by whether the aneurysm or dissection had ruptured and by type of repair (surgical versus endovascular). Results—: We identified 91 212 patients who had repair of an aortic aneurysm or dissection. SCI occurred in 235 cases (0.26%; 95% confidence interval [CI], 0.22%–0.29%). In patients with ruptured aneurysm or dissection, the rate of SCI was 0.74% (95% CI, 0.60%–0.88%) compared with 0.16% (95% CI, 0.13%–0.19%) with unruptured aneurysm. In secondary analyses, rates of SCI were similar after endovascular repair (0.91%; 95% CI, 0.62%–1.19%) compared with surgical repair (0.68%; 95% CI, 0.53%–0.83%; P =0.147) of ruptured aortic aneurysm or dissection; however, rates of SCI were higher after surgical repair (0.20%; 95% CI, 0.15%–0.25%) versus endovascular repair (0.11%; 95% CI, 0.08%–0.14%; P <0.001) of unruptured aneurysm. Conclusions—: SCI occurs in ≈1 in 130 patients undergoing aortic dissection or ruptured aortic aneurysm repair and in 1 in 600 patients undergoing unruptured aortic aneurysm repair.